The meaning and symbolism of st. Ambrose Mediolanius, the hiearach of the East and the West, to Serbian orthodox church with reflection on iconographic compositions and art - Андрејић, Живојин Р. (Sabornost - The Theological Year-book, 2013)
Fresco program of the oldest and the most important lauras, and at the time before founding of Serbian autonomity, represents the expression of religious and ethic, as well as social and poplitical principle that permeate each other with clearly formed church-state manifesto that was created by the future first Serbian archbishop. The apearance and meaning of St. Ambrose and martyr Iliric can be understood only if we take into consideration the religious meaning and the spiritual background and social and poolitical momentum during founging of Serbian church at the end of th XII and beginning of the XIII century. Obeying a specific religious and ethic demands, St. Sava acted in accordance with the his socio-political position, where he coud predict the development of Serbian state in the future. The reasons of St. Sava to show great respect to St. Ambrose and great saints in the region of Sirmium were of deeper nature. Primarily, tradition, values and rights he wanted the Serbian church to achieve by practicing of early Christian heritage of former province of Ilirik, the episcopacy Sirmium, Morava and Naisus, as well as the archdiocese Justiniana Prima, later the archdiocese of Ohrid, to which Serbian lands used to be subjected to. After proclaming the autonomy of Serbian church, to these directions, where other Serbian ethnic space had been, Serbian state spread, as well as its church, during XII and XIV centuries.